Autoimmune diseases in patients with vitiligo - Seminario, Violeta (1995)
We studied 51 patient from Lima and other peruvian districts with vitiligo, acquired idiopatic illness, that is due to gradual melanocyte destruction and immunological disturbances. The purposes were the early diagnosis of other associated autoimmune diseases and to do a clinic pathological correlation including family data. We studied circulating autoantibodies and skin biopsis in immunomicroscopy. Generalized vulgaris vitiligo was the most frequent type of vitiligo. The 33.3% of all the cases had other associated autoimmune disease and 37.2% hypersensitivity I disease. The 19.6% has family members with vitiligo and 31.2% with other autoimmune diseases.